Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/we.2734
|View full text |Cite
|
Sign up to set email alerts
|

A reinforcement‐learning approach for individual pitch control

Abstract: Individual pitch control has shown great capability of alleviating the oscillating loads experienced by wind turbine blades due to wind shear, atmospheric turbulence, yaw misalignment, or wake impingement. This work presents a novel controller structure that relies on the separation of low-level control tasks and high-level ones. It is based on a neural network that modulates basic periodic pitch angle signals. This neural network is trained with reinforcement learning, a trial and error way of acquiring skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The blade load-based estimator is verified numerically. What we consider as the true measurements of the out-of-plane bending moments are provided by LES performed with an in-house wind turbine simulation environment (Chatelain et al, 2017;Balty et al, 2020;Coquelet et al, 2022). The latter relies on a Vortex Particle-Mesh method (Chatelain et al, 2013) in which wind turbine blades are modeled by Immersed Lifting Lines (Caprace et al, 2019).…”
Section: Simulation Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The blade load-based estimator is verified numerically. What we consider as the true measurements of the out-of-plane bending moments are provided by LES performed with an in-house wind turbine simulation environment (Chatelain et al, 2017;Balty et al, 2020;Coquelet et al, 2022). The latter relies on a Vortex Particle-Mesh method (Chatelain et al, 2013) in which wind turbine blades are modeled by Immersed Lifting Lines (Caprace et al, 2019).…”
Section: Simulation Environmentmentioning
confidence: 99%
“…Russell et al (2024) additionally demonstrated how LiDAR-assisted feedforward individual pitch control was improving load alleviation results for turbines operating in freestream conditions. Coquelet et al (2022) investigated the case of waked turbines and concluded that it provided challenges, calling for new IPC schemes accounting for partial or total wake impingement. When it comes to wake mixing, the controllers act in a dynamic way.…”
mentioning
confidence: 99%
“…Strategies based on learning methods such as neural networks and reinforcement have been proposed e.g. in [6], [7], iterative learning control in [8], neural based PID controllers in [9], feed-forward model predictive control, in [10], and adaptive high order sliding-mode controller [11]. The direct control of the blade using local inflow measurements has been studied in [12] and cascaded controllers has been proposed in [13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical approaches offer a convenient framework for investigating IPC strategies. The highest fidelity tools that also capture the wake response usually consider Large Eddy Simulation (LES), combined to discrete type line approaches [5,6], such as the Actuator Line (AL) or Lifting Line methods. The use of these wind turbine models remains computationally affordable at the scale of a small wind farm.…”
Section: Introductionmentioning
confidence: 99%